Étude morphologique, systématique et écologique des Serpulidae (Annelida Polychaeta) de la région de Marseille. - Zibrowius, H. (Recueil des Travaux de la Station marine d'Endoume, 1968)
The Serpulid fauna of the Mediterraneen is rather insufficiently known. The present study of this family is based essentially on new samples in submarine caves (which are a biotop notably rich in Serpulids) in the Marseilles region together wlth several samples made in other biotops. On the whole about 40 species are examined including almost all species previously recorded in the Mediterranean. Six species are described: Serpula massiliensis n.. sp., Vermiliopsis undulata n. sp. Omphalopoma annulata n. sp. Josephella carenata n. sp. Spirorbis (Laeospira) heteropoma n. sp., Spirorbis (Laeospira) endoumensis n. sp. Some other species were found for the first time since they were described or are now identified with certitude and re-exammed: Hydroldes helmatus. Vermiliopsls agglutinata., Spirobranchus lima Vermiliopsis rugosa. Omphalopoma cristata, Omphalopoma gracilis. The last species is new for the Mediterranean as well as Hydroides inornatus (?), Hyalopomatopsis sp., Spirorbis (Paralaeospira) striatus, and Spirorbis (Laeospira) cuneatus. It was necessary to transfer some species to other genera (Vermiliopsis rugosa. Omphalopoma gracilis, Spirobranchus lima, Spirobranchus polytrema), to introduce a new specific name (Hydroides pseudouncinata n.n..) and to change another one (Placostegus crystallinus instead of P. tridentatus) and to complete diagnoses of numerous species and genera. A key is given to Mediterranean species. ln addition to the discussion of the morphology and the systematics an attempt was made to describe the general distribution of each species.
World Polychaeta Database (WPolyDb). Not known to be available online, except here.